Learning of complex and critical thinking - Rutar Ilc, Zora (Šolsko polje, 2007)
All advanced school systems and didactic approaches stress the importance of active learning, problem approach, communication and collaboration skills development, partnership and dialogue, research, organizing, critical and creative thinking. In the present paper we will think about three levels of assuring such a learning environment that will help to develop complex and critical thinking. The first level refers to the classroom practise: how a teacher can add to complex and critical thinking development with different approaches to planning and doing. The second level refers to the level of individual schools: how can schools in the context of their vision and developmental planning assure such a climate which will enable development of complex and critical thinking. The third level refers to school policy, the prevailing pedagogical discourse or paradigm conflict and also wider social conditions as a broadest frame which prescribes the limits of possibility and the ability to reflect and exceed them. None of these levels can be omitted toensure complex and critical thinking otherwise the whole "enterprise" will fail.
Keywords: kritično mišljenje; metodika; pouk; retorika; učenje